Development of the TTMCT Instrument and In-Depth Interview Activities to Identify Misconceptions about the Periodic Table Concept - YOSEPHINE DEBBIE DAMAYANTI; Endang Susilaningsih; Sigit Priatmoko (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang, 2025)
Misconceptions arise when students hold ideas that conflict with scientifically accepted concepts, and persistent misconceptions can reduce learning outcomes and weaken conceptual understanding. This study analyzed students’ misconceptions about the Periodic System of Elements through the development of a Three-Tier Multiple Choice Test (TTMCT) and supporting in-depth interview activities. A quantitative design was applied. Data were collected through observation, diagnostic testing, interviews, questionnaires, and documentation. Content validation involved eight experts (chemistry lecturers and chemistry teachers) and was followed by a small-scale trial to evaluate item clarity and practicality. The main study was conducted in five public and private schools and involved 250 Grade X students. TTMCT results indicated that a substantial proportion of students demonstrated misconceptions, distributed across seven distinct misconception profiles revealed by the combination of answer choice, reasoning selection, and Certainty of Response Index patterns. Interview findings helped confirm the diagnostic classifications and clarified typical reasoning used by students. Overall, the developed TTMCT instrument, complemented by in-depth interviews, proved effective for identifying and mapping misconceptions on periodic table concepts, providing diagnostic information that can guide targeted instructional remediation. Such mapping supports teachers in prioritizing concepts that require reteaching.